Pengaruh Lingkungan Kerja dan Kompensasi terhadap Kepuasan Kerja Karyawan PT. Mekar Abadi Sentosa Jombang - Bachtiar Yahya; Sulastri Irbayuni (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study was to analyze the effect of work environment and compensation on job satisfaction of employees at PT. Mekar Abadi Sentosa Jombang. This research method uses quantitative research where the dependent variable is job satisfaction and the independent variable in this study is the work environment and compensation. Sampling used quantitative methods with saturated sampling technique and data analysis was carried out using the Partial Least Square (PLS) method. The results of the analysis of this study that the work environment and compensation have a positive and significant effect on job satisfaction of employees at PT. Mekar Abadi Sentosa Jombang. The results of the discussion of this study explain that the better the work environment and compensation, the higher the job satisfaction. Keywords: Work Environment, Compensation, and Job Satisfaction